1965
DOI: 10.1017/s0080456800023450
|View full text |Cite
|
Sign up to set email alerts
|

VII.—Nuclear Phenomena in Marasmius androsaceus (L. ex Fr.) Fr. and M. rotula (Scop. ex Fr.) Fr.

Abstract: Due to the overwhelming enthusiasm about the meetings, participants suggested setting up a communication network for researchers and professionals, and an organizational framework for a biannual conference. Interested persons should send their addresses, disciplines, and research areas to me care of School of Architecture and Urban Design, University of Kansas, Lawrence, KS 66045. David C. Saile, University of Kansas.D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1968
1968
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…As this happens, the old nuclear envelope constricts just behind one of the daughter nuclei (Figs. 4-5, [11][12][13][14]. The other daughter nucleus now begins to migrate, usually in the opposite direction, and, as it does so, the old envelope becomes attenuated and fades from view (Figs.…”
Section: Observations On Living Cells Of C Fagacearummentioning
confidence: 99%
“…As this happens, the old nuclear envelope constricts just behind one of the daughter nuclei (Figs. 4-5, [11][12][13][14]. The other daughter nucleus now begins to migrate, usually in the opposite direction, and, as it does so, the old envelope becomes attenuated and fades from view (Figs.…”
Section: Observations On Living Cells Of C Fagacearummentioning
confidence: 99%
“…Also from a genetic viewpoint it is difficult to liken a transverse constriction to the division of an elongated nucleus. The same difficulty is encountered by Duncan & Macdonald (1967), who describe a transverse constriction in the nuclear division of Marasmius androsaceus (Basidiomycetes).…”
Section: Discussionmentioning
confidence: 70%
“…Duncan et al5 obtained AlPO 4 -H1 by a similar Downloaded by [University of South Florida] at 12:18 09 October 2014 The single phase AlPO 4 -H1 was obtained when the molar ratio of the aluminophosphate gels (revealed that the sample calcined at 800 • C had a stoichiometric composition; Al 2 O 3 (42.8%), P 2 O 5 (56.5%) with an atomic ratio Al/P = 1.06.…”
mentioning
confidence: 89%
“…1,2 The irradiation of microwave enhances molecular rotation and creates heat caused by the friction of the molecules. Template-free synthesis of AlPO 4 -H1 was reported by Duncan et al 5 by conventional heating. The microwave hydrothermal reaction has been applied to the synthesis of zeolites 3 and aluminophosphate molecular sieves (AlPO 4 s), where the effect of the use of microwave heating was found in the preparation of large AlPO 4 -5 crystals 4 and in rapid synthesis.…”
Section: Introductionmentioning
confidence: 98%